A comparison of reproductive outcomes of patients with adenomyosis and infertility treated with High-Intensity focused ultrasound and laparoscopic excision. (1st January 2020) - Huang, Yu Fu; Deng, Jia; Wei, Xue Li; Sun, Xin; Xue, Min; Zhu, Xiao Gang; Deng, Xin Liang
Abstract: Objective: The aim of this study was to compare the treatment effects of high-intensity focused ultrasound (HIFU) and laparoscopic excision (LE) in patients with adenomyosis and infertility. Materials and methods: A total of 93 patients with adenomyosis and infertility who were treated with HIFU (50 patients) or LE (43 patients) from January 2012 to January 2017 at the Third Xiangya Hospital of Central South University were retrospectively analyzed. Clinical characteristics including dysmenorrhea severity pain score, menorrhagia severity scores, reproductive outcomes, complications during pregnancy and delivery, adverse effects, surgical complications, and other clinical variables were compared between the HIFU and LE groups. Results: Of the total 93 patients with adenomyosis and infertility, 50 were treated with HIFU and 43 underwent LE. Both HIFU and LE treatments achieved significant relief of dysmenorrhea and menorrhagia. The total hospital stay was shorter in patients treated with HIFU than in those who underwent LE surgery. Neither HIFU nor LE treatment led to severe complications after treatment. Most importantly, patients treated with HIFU showed significantly higher pregnancy rates and natural conception rates than those who underwent LE surgery. Notably, in the HIFU treatment group, those with diffuse adenomyotic lesions had significantly lower postoperative pregnancy rates than those with focal adenomyosis. Conclusion: HIFU showed a safe and effective profile as a therapeutic management option for patients with adenomyosis. In comparison with LE, HIFU treatment achieved better postoperative reproductive outcomes. HIFU treatment should be encouraged and implemented in clinical practice.